Individual liberty, safety and police liabilities under the Mental Health (Care and Treatment) Act - CHAN, Gary Kok Yew (Institutional Knowledge at Singapore Management University, 2025)
How should a society strike a balance between the objective of ensuring safety from dangers that may be posed by individuals believed to have a mental disorder and the deprivation of their liberty? How should police officers discharge their duties in apprehending such individuals with a view to conveying them to a medical practitioner at a psychiatric institution? These legal issues took centrestage in the Singapore High Court decision of Mah Kiat Seng v Attorney-General in which the apprehended individual brought claims in false imprisonment against a police officer. The decision examined the underlying purposes of the Singapore Mental Health (Care and Treatment) Act, the right of the person to be informed of the grounds of apprehension, the bases of the police officer’s belief that the person posed a danger to himself or others, and the circumstances in which the police officers may be entitled to immunity from liability to civil or criminal proceedings. The High Court judgment led to statutory amendments to clarify police duties when apprehending such individuals and discussions about enhancements to police training and crisis support services for persons with mental illnesses. With reference to the law and/or policy in Australia and the UK, the paper critiques the judicial findings, the statutory amendments and policy alternatives.